Factors affecting the profitability of Malaysian commercial banks - Ong, Tze San; Teh, Boon Heng (Academic Journals, 2013)
This study intends to investigate the impact of bank-specific characteristics and macroeconomic conditions on Malaysian commercial banks financial performance, during the period of 2003 to 2009. This study employs regression models that relate bank profitability ratios to various explanatory variables. There are three ratios which represent profitability measures are return on assets (ROA), return on equity (ROE) and net non-interest margin (NIM). Seven variables are drawn from the conventional banking literature as proxies for bank-specific and macroeconomic factors. Results of this study indicated that ROA is the best profitability measures. All bank-specific determinants affect bank profitability significantly in the anticipated way. However, no evidence is found in support of the macroeconomic variables have an impact on profitability.